The Regulation of Bone Resorption in Tooth Formation and Eruption Processes in Mouse Alveolar Crest Devoid of Cathepsin K - Masayo Okaji; Hideaki Sakai; Eiko Sakai; Mitsue Shibata; Fumio Hashimoto; Yasuhiro Kobayashi; Noriaki Yoshida; Kuniaki Okamoto; Kenji Yamamoto; Yuzo Kato (Elsevier, 2003)
Osteoclastic bone resorption has recently been implicated in the tooth formation and eruption in alveolar bone. Cathepsin K (CK) is a cysteine proteinase expressed predominantly in osteoclasts and is believed to play a critical role in degradation of bone matrix proteins. Here we present evidence that the alveolar bone resorption is essential for the tooth formation and that eruption proceeds normally in CK-deficient (CK-/-) mice. Radiographic and histological analyses revealed that the alveolar bone from these animals had no significant abnormalities during the tooth development between 5 and 28 days after birth. The tooth crown was normally erupted through the alveolar bone layer at 28 days after birth. The number of tartrate-resistant acid phosphatase-positive multinuclear cells in the alveolar bone around the tooth germ was apparently increased in 5-day-old CK-/- mice compared with age-matched littermates. More important, however, the immunohistochemical localization of matrix metalloproteinase-9 (MMP-9) was clearly increased in the CK-/- osteoclasts. In contrast, no significant difference in the immunoreactivity for cathepsin D was observed between the CK-/- osteoclasts and the wild-type ones. These results indicate that CK-/- osteoclasts are fully differentiated and are capable of degrading the organic phase of alveolar bone during the tooth formation and eruption, which may result from the compensatory action by MMP-9 increasingly expressed in the osteoclasts.